An examination of the share price and trading volume behaviour on the exdividend date for securities list - Noreh, Michelle (Strathmore University, 2016)
In a semi-strong form efficient market, the shareholder who sells shares cum-dividend should have the same gain as the one who holds on to the same shares which drop to the ex-dividend price, and receives the dividend. This implies that stock prices should fall by the exact amount of the dividend payment on the ex-dividend day in an efficient market, and suggests that there should be abnormal trading volumes around the ex-dividend day to bring down the share prices by the dividend amount. Empirical studies have, however, had varying findings in different markets. While some empirical studies have found the share price to fall by the dividend amount on the ex-dividend day, the majority find that the ex-dividend price behaviour is a price reduction by less than the dividend amount, which is an anomaly when the efficient market hypothesis is taken into account, since from theory the share price should fall by the amount of dividend, on average. Yet other studies have found that the share prices rise on the ex-dividend day. An event study was carried out on price and volume behaviour 5 days before and 5 days after the ex-dividend day as well as how long it took the prices to normalize after the ex-dividend day. The study examined the cash dividends by companies listed on the Nairobi Securities Exchange for the period from September 2006 to November 2015 and found that, on average, the share prices fell by only 20% of the dividend amount on the ex-dividend day, and there were abnormal share volumes of -1% traded on this day. It was also found that the prices did not normalize and actually rose on average within the 5 day period after the ex-dividend day. These findings suggest that the market is not efficient in the semi-strong form and there are likely to be arbitrage opportunities in the Kenyan market, and thus an investor can buy a share cum-dividend, receive the dividend, and sell the share ex-dividend, at a price higher than the expected ex-dividend price.
Submitted in partial fulfilment of the requirements for the Degree of Master of Commerce at Strathmore University
Keywords: Share price; Trading volume behaviour; Ex - dividend; Nairobi Securities Exchange